In vitro exoproteome profile of Stenotrophomonas maltophilia in iron depleted condition - Azman, Adleen (2015)
Stenotrophomonas maltophilia has been recently identified as the third most common nosocomial infection in the hospital especially among immunocompromised patients. Management of S. maltophilia infection is an inordinate challenge in the hospital due to its intrinsic and acquired resistance to most of the antibiotics. Although S. maltophilia is frequently associated with increased morbidities and mortalities, the pathogenesis mechanisms of S. maltophilia are still not very clear. This is due to S. maltophilia which entered hospital setting from environmental sources heavily colonizes the respiratory tract and other anatomical sites, without showing a clear cut infection in human. Hence, the debate about whether S. maltophilia is a true pathogen or a colonizer is still an ongoing investigation. Iron is an essential factor for their survival. In the host environment, the level of iron is ~1011 times below than the level required for microorganism and is mostly unavailable as it is bound together with host protein. Microbes develop multiple mechanisms such as siderophores secretion to forage for free iron in an iron limited environment. Under iron starvation, microbes also secrete other virulence potential exoproteins. The present study was aimed at investigating the effect of iron depletion in secretion of proteomes in S. maltophilia. Briefly, four strains of the S. maltophilia LMG959 (environment), ATCC 13637, CS17 and CS24 (clinical) were grown in normal and iron depleted medium. The siderophores production was screened qualitatively and quantitatively using CAS plate and liquid assay. Followed by, nematocidal assay was performed to test the ability of S. maltophilia supernatant grown in iron depleted medium to kill the nematode Caenorhabditis elegans. Lastly, the putative proteins expressed during the stressed condition were identified by Isobariq Tags for Relative and Absolute Quantification (ITRAQ) mass spectrometry. Initial screening of siderophores production exhibited largest yellow zone for CS17 and CS24 (10 mm) followed by ATCC13637 (8 mm), LMG959 (6 mm). The siderophores production was further confirmed quantitatively and the highest was detected in both clinical isolates (30.8% [p<0.05] and 29.4%) at 72 h followed by ATCC 13637 (8%) and LMG959 (4%) in iron depleted medium (p>0.05). Isolates grown under iron-depleted condition (ATCC 13637: 63%; CS17: 96%; CS24: 97%) showed more nematocidal activity than in normal condition (ATCC 13637: 43%; CS17: 76%; CS24: 79%) (p>0.05). None of the worms were killed when infected with LMG959. Based on the above result, only CS17 and LMG959 are subjected to ITRAQ analysis. ITRAQ analysis revealed a total of 122 proteins showed altered expression in response to iron starvation with 96 being up-regulated and 26 were down-regulated for both isolates. ITRAQ analysis identified higher expression of several iron acquisition and pathogenic potential proteins in both isolates grown in iron depleted condition. In another study, clinical and environment isolates grown under normal condition were compared to identify the proteomic profiles. ITRAQ analysis discovered 81 proteins that exhibited differently expressed with 40 proteins up-regulated and 41 proteins down-regulated. In normal condition, several proteins such as Elongation factor G, Endoribonuclease and Fimbrial protein expressed in higher fold in clinical isolate compared to environmental isolate. In conclusion, S. maltophilia produced siderophores under iron depleted condition. Based on nematocidal assay, eventhough there is no significant difference in killing rates between iron depleted and normal condition but S. maltophilia did show an increased of ~20% of its killing rates in iron depleted medium except for LMG959. ITRAQ analysis revealed S. maltophilia altered the expression of metabolic, iron acquisition and pathogenic potential proteins under iron starvation. A comparison of clinical and environmental isolates grown in normal medium revealed that clinical isolates expresses more pathogenic potential proteins compared to environmental isolate. The data obtained in the present study, clearly indicates that under iron depleted condition, S. maltophilia are capable of altering the expression of its proteomes to ensure their survival in the host.